Alginate Microsphere as a Delivery System and Adjuvant forAutoclaved Leishmania majorand Quillaja Saponin: Preparationand Characterization: Microspheres for antigen delivery - Tafaghodi, Mohsen; Sajadi Tabasi, Syyed Abolghasem; Payan, Maryam (Iranian Journal of Pharmaceutical Sciences, 2007)
The goal of this study was to prepare and characterize alginate microspheres asan antigen delivery system and adjuvant for immunization against leishmaniasis.Microspheres encapsulated with autoclaved Leishmania major(ALM) and Quillajasaponin (QS) were prepared by an emulsification technique and characterized forsize, encapsulation efficiency and release profile of encapsulates. Selection ofappropriate parameters (viscosity of alginate, emulsifier and sonication times)enabled the preparation of alginate microspheres with a mean diameter of 1.92±1.0μm, as determined by scanning electron microscopy and particle size analyzer. Theencapsulation efficiency was about 34.2±6.7% for ALM and 31.0±4.4% for QS, asdetermined by spectrophotometric assays.In vitro release profile showed a slowrelease rate for encapsulated ALM and QS, 35.7±8.7% of ALM and 36.9±4.7% ofQS were released during 1 week. The molecular weight was evaluated by SDS-PAGEand showed that the process of encapsulation did not affect the molecular weightof the entrapped antigen. With regard to the optimum diameter (less than 5 m), slowrelease rate and preservation of antigen molecules, formulated alginate microspherescould be considered as a promising antigen delivery system and adjuvant for ALMand QS.